(untitled) (Revista Educação, Artes e Inclusão, 2024)
The aim of this study was to explore the real situation of the inclusion process of people with some disabilities (PwD) in the labor market at São Paulo ABC region. Questionnaires were applied to employees and employers persons who are responsible for hire people, as well the people who have a higher position at the company. The study was divided into two phases: the exploratory as the first one and the analytical-descriptive as the second one. Quantitative and qualitative techniques of data collection and analysis were applied. The Game of theory was used in order to confirm the occurrence of influences, and how they acted in the decision making process of hiring PwD. The inclusion of PwD in the labor market in ABC companies mostly obeys the quota law. Structural changes in labor relationship are necessary, without which the applicability of the planned measures would only have a palliative effect. We emphasize the growing need for research aimed the understanding and analyzing the new professional reality within work organizations, both in the evaluation and questioning of existing practices and to invent new possibilities for hiring PwD professionals.